2016
DOI: 10.1111/jsap.12591
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic concentrations of copper and other metals in dogs with and without chronic hepatitis

Abstract: Dogs with chronic hepatitis not only have increased concentrations of copper in the liver but also increased concentrations of cobalt, manganese and zinc; measurement of these elements may perhaps aid in diagnosis of liver disease in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
0
15
0
5
Order By: Relevance
“…In some cases, variations in these trace elements have been proposed as markers of disease and indicative of prognosis [ 30 , 31 ]. The most extensive information is available for Cu, and excessive Cu accumulation in the liver is known to occur in dogs suffering from hepatic disorders [ 3 , 4 , 5 , 6 , 7 , 8 ]. Serum copper concentrations are also higher in human patients suffering from hepatic disorders [ 31 ], and elevated Cu:Zn ratios have been proposed as markers of disease in patients with hepatic cirrhosis [ 31 ] or hepatocellular carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, variations in these trace elements have been proposed as markers of disease and indicative of prognosis [ 30 , 31 ]. The most extensive information is available for Cu, and excessive Cu accumulation in the liver is known to occur in dogs suffering from hepatic disorders [ 3 , 4 , 5 , 6 , 7 , 8 ]. Serum copper concentrations are also higher in human patients suffering from hepatic disorders [ 31 ], and elevated Cu:Zn ratios have been proposed as markers of disease in patients with hepatic cirrhosis [ 31 ] or hepatocellular carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although information in animals is scarcer, it is expected that trace elements are also involved in the pathogenesis of numerous diseases. For example, Cu [ 3 , 4 , 5 , 6 , 7 ] and other trace elements [ 8 ] are known to play a role in chronic hepatitis in dogs, and elevated concentrations of Fe and Cu (capable of inducing oxidative damage) have been detected in the brain tissues of Alzheimer’s patients and in the brains of humans and animals affected by other neurological disorders [ 9 , 10 ]. A recent study in dogs has suggested the role of Mn, Se and Zn in the pathophysiology and/or treatment of epilepsy, and that anti-convulsant therapy may affect Cu and Mo metabolism [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing frequency of CH cases beginning in the late 1990s correlates with the change in the premixes used to supplement Cu in commercial dog foods, which resulted in higher amounts of bioavailable Cu in diets . The panel believes that the National Research Council (NRC) and Association of American Feed Control Officials dietary guidelines, along with a change to more bioavailable Cu chelate premixes in commercial dog food, are linked with an increased prevalence of hepatic Cu accumulation in dogs (Table ) .…”
Section: Etiologymentioning
confidence: 99%
“…correlates with the change in the premixes used to supplement Cu in commercial dog foods, which resulted in higher amounts of bioavailable Cu in diets. 8,21,36,46,120,121 The panel believes that the National Research Council (NRC) and Association of American Feed…”
Section: Drugs and Toxinsmentioning
confidence: 99%
“…A intoxicação por cobre tem sido relatada tanto em humanos como em animais, principalmente na espécie ovina, a mais suscetível e frequentemente acometida [7,11,12]. Em cães, as manifestações clinicopatológicas da intoxicação por cobre são caracterizadas, basicamente, por um quadro de insuficiência hepática crônica, fazendo da crise hemolítica, tão comum em ovinos intoxicados por cobre, uma síndrome raramente associada à intoxicação na espécie canina, existindo apenas ocasionais descrições na literatura veterinária a cerca dessa manifestação [2,3,6,11,17]. O objetivo deste relato é descrever um caso de crise hemolítica em um cão com hepatite crônica associada ao cobre.…”
Section: Introductionunclassified